Anionic ring-opening polymerization of isobutylene oxide initiated with potassium salts activated by 18-crown-6: Determination of mechanism and characterization of polyether monols and diols - Zbigniew Grobelny; Justyna Jurek-Suliga; Sylwia Golba (eXPRESS Polymer Letters, 2022)
Various potassium salts, i.e., KOH, HOC3H6OC3H6OK, CH3OK, i-PrOK, t-BuOK, CbK, and (Me3Si)2NK activated by 18-crown-6 appeared to be active initiators of first anionic polymerization of isobutylene oxide. The processes were performed in mild conditions, i.e., tetrahydrofuran solution at room temperature under normal pressure. The polymers obtained are polyether-monols or -diols also containing macromolecules with starting groups having double bonds (12.5–46.6 mol%). It was stated that polymer unsaturation results not only from chain transfer reaction to monomer but mainly from deprotonation of monomer by an initiator, which behaves in the polymerizations as nucleophilic bases. In all systems, isomerization of the double bonds is also observed. Most of the obtained polymers are crystalline, insoluble materials with crystalline content up to 52.47% for a derived sample with potassium i-propoxide as initiator. The proneness of the polyisobutylene oxide to form crystal–type package is influenced by the average molar mass of the polymers. They are bimodal with Mn = 400–1300 (Mcalc = 1440) and very low dispersities (Mw/Mn = 1.01–1.12). 13C NMR, MALDI-TOF, FTIR, SEC, XRD, and DSC techniques were used for polymers analysis. A mechanism of the processes studied was proposed.